The 1720 imperial festival in Istanbul: Festivity and representation in the early eighteenth-century Ottoman Empire - Erdoğan, Sinem. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2017., 2017)
This dissertation focuses on the 1720 imperial circumcision festival that was held in Istanbul during the reign of Ahmed III (r. 1703-1730). It intends to present the first comprehensive monograph on an Ottoman imperial festival through a holistic approach. This study addresses the ideological motives behind the Ottoman court’s commissioning of this massive scale festival at this particular period, as well as exploring in-depth how it was planned, organized, staged and represented. Due to its holistic approach, this dissertation combines the methodological tools of history, art history and performance studies, and, thus offers an interdisciplinary perspective to the subject. For the first time in the field it introduces a wide range of archival source basis to the study of an imperial festival. These sources are considered with the textual and pictorial narratives of the festival that are analyzed in terms of their codicology, iconography and narratology. The scrutinized analysis of the rites of the 1720 circumcision festival and its representation in illustrated festival books brings to light hitherto unknown material, social, financial and semiotic aspect behind the planning of an imperial festival. At the same time it foregrounds substantial information on the Ottoman bureaucracy’s organizational capacities as well as mobilization of human and material resources across the empire. In addition, this study illustrates the fascinating social dimension of the event, by unearthing the modes of involvement of ordinary people as contributors and as beneficiaries of the festival. This challenges the strictly state centered approach towards court commissioned festivals in the Ottoman Empire.
Keywords: Circumcision -- Social aspects -- Turkey.; Circumcision -- Religious aspects -- Islam -- Early works to 1800.; Festivals -- Turkey -- Istanbul.